DISTANCE EDUCATION AND SOCIAL MEDIA LEARNING: UNDERGRADUATE PERCEPTIONS - Zainal Fikri Zamzuri; Syamsul Ariffin Yahaya; Azlan Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2022)
The proliferation of social media in todays’ setting has also permeated into theeducation realm. Social media technology on various platforms has presented anotheralternative tool for adult learners to learn and improve in their studies. The fast technologicaladvancement and expansion have allowed educational practitioners, instructors, trainers, andlearners to utilize the multitude of technology-supported learning tools to ease the teaching andlearning process. These social media platforms have been touted to have huge benefits andpotential for adult learning in the distance education environment. However, to understand thebenefits, this study intends to shed some light on how adult learners perceive social mediaplatforms and their potential use in the learning process and outcomes. Little is known abouttheir social media knowledge and expertise, or their interest in using these platforms forlearning, collaboration, and interaction. The available technology does not ensure successunless it is properly designed and implemented. It is to avoid the risk of being technologicallydriven and not pedagogically driven as it is supposed to be. The result indicates that the adultlearners are very much open to the various social media platforms but they are inclined towardsthe more accustomed ones and not without proper considerations.